Ansai peasant paintings: inheritance of Chinese primitive culture and primitive philosophy - Yaqian Chang; Liming Zhou; Peng Lu; Samina Yasmeen (Trans/Form/Ação)
Chinese primitive philosophy, as the unity of cosmological ontology, epistemology and methodology of the Chinese philosophical system, is a complete and mature philosophical system formed in the late primitive society as early as before the Xia, Shang and Zhou Dynasties. It is also the unity of the concept of Yin and Yang and constant life that is sublimated from the human-beings’ basic cultural consciousness: life consciousness and reproduction consciousness. The Chinese primitive culture, from the painted pottery culture 7,000 years ago to today, from the underground archaeological culture to the group culture on the ground, is a plastic art based on the concept of viewing objects and taking images. It is a broad concept of fine arts that determines the philosophical view, artistic view, emotional temperament, psychological quality and national spirit of the Chinese nation. The most primitive culture and primitive philosophy in China have been preserved with extremely rich and complete historical remains in the group's cultural and social life. It is for this reason that China is the only country with an ancient history of civilization that has not experienced a cultural break. The primitive culture and philosophical system of China, as the philosophical basis and main connotation of ethnic group culture, are completely accumulated in the ethnic groups’ social life. Folk art, which has accumulated the hundreds of millions of working masses’ wisdom in China, is the mother of the Chinese national culture and art that has been inherited from primitive society until today with distinct national and regional characteristics. It is a long-standing cultural form with the longest history, the widest mass participation, the most distinct regional characteristics and the richest cultural connotation in the Chinese national cultural form. The rapid development of the times makes the traditional folk customs and folk arts, which are generally deposited in the rural areas of China, become precarious. As a result, the research advantages of the unique human culture and the original culture of China will cease to exist. Therefore, it is an urgent historical task to make use of this advantage to study the original culture of China and the philosophical genes of the Chinese nation. Protection is imminent, and inheritance is the historical mission, which highlights the deeper significance of studying primitive culture and primitive philosophy in modern society.